2016
DOI: 10.1038/ncomms12158
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic clonal equilibrium and predetermined cancer risk in Barrett’s oesophagus

Abstract: Surveillance of Barrett's oesophagus allows us to study the evolutionary dynamics of a human neoplasm over time. Here we use multicolour fluorescence in situ hybridization on brush cytology specimens, from two time points with a median interval of 37 months in 195 non-dysplastic Barrett's patients, and a third time point in a subset of 90 patients at a median interval of 36 months, to study clonal evolution at single-cell resolution. Baseline genetic diversity predicts progression and remains in a stable dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
85
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(95 citation statements)
references
References 32 publications
7
85
0
Order By: Relevance
“…For example, early driver mutations may become obsolete once the tumor is established, or may even hinder the tumor at later stages so their loss becomes positively selected for. Hints of changing selective pressures on particular aberrations have recently been observed for Barrett's esophagus (Martinez et al 2016). Loss of a copy of CDKN2A seemed to provide a fitness advantage for clones experiencing acid reflux but a disadvantage when the acid is suppressed under treatment.…”
Section: Discussionmentioning
confidence: 99%
“…For example, early driver mutations may become obsolete once the tumor is established, or may even hinder the tumor at later stages so their loss becomes positively selected for. Hints of changing selective pressures on particular aberrations have recently been observed for Barrett's esophagus (Martinez et al 2016). Loss of a copy of CDKN2A seemed to provide a fitness advantage for clones experiencing acid reflux but a disadvantage when the acid is suppressed under treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, fewer than 20% of specific variants overlap between adjacent BE and EA, so either the cancer clone diverged at an early stage or originated separately 53,70 . Analysis BE patients suggested that the genetic diversity of different clones did not change significantly over time, but the extent of divergence of clones at baseline was the strongest predictor of progression 77 .…”
Section: Somatic Mutations That Affect Be Progressionmentioning
confidence: 99%
“…Two studies measured the SCNA rate and clonal dynamics of Barrett’s esophagus (34,45) – a dysplastic condition that has a risk of transforming into invasive carcinoma. In the first study, multiple biopsies from four or more timepoints were subject to analysis with SNP arrays – phylogenetic methods were used to estimate the SCNA rate.…”
Section: Somatic Copy Number Alteration Ratementioning
confidence: 99%